THE EXPORT ENTREPRENEURSHIP OF MSMES ACCORDING TO THE GENDER PERSPECTIVE OF THEIR OWNERS - Garizurieta Bernabe, Jessica; Gazca Herrera, Luis Alejandro (Semestre Económico, 2024)
In order to identify gender gaps in the export entrepreneurship of MSMEs, we conducted a mixed study with a sequential explanatory design to assess the possible link between the business owner’s characterization and the different organizational and external factors related to the export process. To this end, a cross-sectional self-administered instrument and personalized interviews were used to explore the perceptions of a sample of MSMEs owners from the state of Veracruz, Mexico. A correlation analysis showed that the type of enterprise has implications for export capability, but there is no significant relation between business owner characterization, export entrepreneurship capability, and external export factors. During a second analysis, by considering the gender gap a consequent variable, the hypotheses of time management and cultural stereotypes being antecedent variables were accepted. It was concluded that the gender gap in export entrepreneurship is found in specific family roles and generally assigned behaviors, and not in characterization factors.